2013
DOI: 10.1016/j.diff.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The combination of glycosaminoglycans and fibrous proteins improves cell proliferation and early differentiation of bovine primary skeletal muscle cells

Abstract: Primary muscle cell model systems from farm animals are widely used to acquire knowledge about muscle development, muscle pathologies, overweight issues and tissue regeneration. The morphological properties of a bovine primary muscle cell model system, in addition to cell proliferation and differentiation features, were characterized using immunocytochemistry, western blotting and real-time PCR. We observed a reorganization of the Golgi complex in differentiated cells. The Golgi complex transformed to a highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Bovine primary skeletal muscle cells were isolated essentially as described [14]. The bovine primary skeletal muscle cells were obtained using fresh muscle samples from Longissimus thoracis (beef sirloin) collected at an industrial abattoir (Nortura AS, Rudshøgda, Norway).…”
Section: Methodsmentioning
confidence: 99%
“…Bovine primary skeletal muscle cells were isolated essentially as described [14]. The bovine primary skeletal muscle cells were obtained using fresh muscle samples from Longissimus thoracis (beef sirloin) collected at an industrial abattoir (Nortura AS, Rudshøgda, Norway).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, different factors influencing myotube formation, e.g., serum type and coating of cell culture ware, were investigated to optimize the differentiation of bovine myoblasts. Up to now, most of the studies employing bovine cell culture models use serum-containing media to induce the differentiation of myoblasts to multinucleated myotubes (Cassar-Malek et al 1999;Kamanga-Sollo et al 2004;Kook et al 2006;Montoya-Flores et al 2011;Ge et al 2012;Lapin et al 2013;Ronning et al 2013;Van Ba and Inho 2013;Lee et al 2014) instead of defined serum-free culture conditions (Muroya et al 2005). Unfortunately, the detailed composition of the serum-free medium used in the study of Muroya et al (2005) was not described.…”
mentioning
confidence: 95%
“…Unfortunately, the detailed composition of the serum-free medium used in the study of Muroya et al (2005) was not described. Ronning et al (2013) showed that a special coating with a combination of glycosaminoglycans and fibrous proteins improves early differentiation of bovine primary skeletal muscle cells. Cassar-Malek et al (1999) investigated the insulin-and T3-regulated proliferation and differentiation of bovine satellite cells.…”
mentioning
confidence: 99%
“…In addition, by using cell models, we can test one specific condition at a time, and are thus able to say that any response noted is most likely due to that condition. We have previously developed a model system using bovine primary skeletal muscle cells [11]. The bovine primary skeletal muscle cells were obtained from a collection of animals of the same age (young animals), gender and breed using hot boned fresh muscle samples obtained immediately after slaughter from Longissimus thoracis (beef sirloin) collected at an industrial abattoir (Nortura AS, Rudshøgda, Norway).…”
Section: Methodsmentioning
confidence: 99%